Information and bargaining through agents: experimental evidence from Mexico’s labor courts - Sadka, J; Seira, E; Woodruff, CM (Oxford University Press, 2024)
Well-functioning courts are essential for the health of both financial and real economies. Courts function poorly in most lower-income countries, but the root causes of poor performance are not well understood. We use field experiments with ongoing cases to analyse sources of dysfunction in Mexico’s largest labour court. We provide parties with personalized predictions for case outcomes and show that this information nearly doubles settlement rates and reduces average case duration. The experiment generates the first experimental evidence in live court cases that reducing information asymmetries results in a decrease in delay, an outcome predicted by many theories of bargaining. We also find that the information treatment is effective only when the plaintiff is present to receive it directly, suggesting agency issues between plaintiffs and their private lawyers. For most workers, the treatment appears to improve welfare, as measured by discounted payouts and ability to pay bills.